1987
DOI: 10.1111/j.1600-0528.1987.tb01742.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing oral health in long term care facilities

Abstract: In a stratified random sample of 41 long term care (LTC) facilities in Vancouver, 653 residents were chosen to investigate oral health needs and demands for treatment. All of the 603 dentists in the same area were questioned to assess their interest in attending the residents of the institutions. The information from each source was reviewed to identify factors influencing the oral health services to this predominantly elderly and medically compromised population. The majority (60%) of the residents were edent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…concurrent validity) or future (i.e. More often than not, patients and respondents to SDIs when compared with clinicians and researchers see the need for health care and treatment quite differently (31), which confirms yet again the need for input from nonexperts when developing psychometric instruments. The instrument is valid when the response elicited (e.g.…”
Section: Criterion Validitymentioning
confidence: 72%
“…concurrent validity) or future (i.e. More often than not, patients and respondents to SDIs when compared with clinicians and researchers see the need for health care and treatment quite differently (31), which confirms yet again the need for input from nonexperts when developing psychometric instruments. The instrument is valid when the response elicited (e.g.…”
Section: Criterion Validitymentioning
confidence: 72%
“…Previous international studies have shown poor oral hygiene and oral health among housebound [3][4][5] and institutionalised older people [6][7][8][9][10][11] . This is even more important for people of an advanced age.…”
Section: Introductionmentioning
confidence: 94%
“…However, despite extensive research on barriers to dental service-use [7,12-17] and oral hygiene-related behavior [18-21] in which barriers have been associated with impaired mobility, impaired activities of daily living, low energy, depression, and lack of social support, it remains unclear how frailty in its many forms influences the oral care of older people. For example, it is not clear whether service-use and toothbrushing are disturbed more by impaired mobility, dexterity, or low morale, or, as some [22,23] suggest, by a lack of time and energy caused by more pressing general health problems. Nor do we know what motivates frail people to apply oral care despite physical and cognitive impairments, or why there are discrepancies between perceived treatment need and service-use.…”
Section: Introductionmentioning
confidence: 99%